The Determinant Factors of Labor. Data Analysis of “Maternal Card Cohort” in Tawangharjo Community Health Center, Grobogan - Purnami, Cahya Tri; Dharminto, Dharminto; Mawarni, Atik; Kurniawati, Yacinta Puji (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
ANC data in the maternal card cohort register at the Puskesmas can be used to detect risk factors for pregnancy and labor that can prevent maternal death, but this data has never been analyzed. This study aims to analyze the determinants of labor in mothers who received ANC by a midwife according to the data in the maternal card cohort. This research is a descriptive-analytic study design using the observational method. Data sourced from the maternal card cohort register that meets the standards of accuracy and completeness of ANC results in records until labor in the 2019 time period. A total of 172 data were used as samples. Maternal characteristics, maternal mortality risk factors, levels of maternal risk factors based on the Poedji Rochjati score as independent variables, and the act of labor is the dependent variable. Univariate and bivariate analysis was carried out descriptively and analytically using the chi-square test. The majority of mothers aged 20-35 years (81.4%), had basic education (94.2%), normal nutritional status (84.9%), hadn’t anemia (80.2%), had normal blood pressure (70, 9%), hadANC visits 5-10 times (65.7%), categorized as low-risk pregnancy (86.6%), and almost all received normal labor in the previous (96.0%). Previous labor and maternal risk factors were associated with the last labor act received by the mother (p-value=0.040; p-value=0.043).Abstrak: Data pelayanan kehamilan (antenatal care) pada register kohort kartu ibu di Puskesmas dapat digunakan untuk mendeteksi faktor risiko kehamilan dan tindakan persalinan yang dapat mencegah kematian ibu, namun belum pernah dilakukan analisis pada data tersebut. Penelitian ini bertujuan menganalisis faktor-faktor penentu tindakan persalinan pada ibu yang mendapat ANC oleh bidan sesuai data pada kohort kartu ibu. Penelitian ini merupakan rancangan studi deskriptif analitik menggunakan metodeobservasional. Data yang digunakan bersumber pada register kohort kartu ibu yang memenuhi standar ketepatan dan kelengkapan catatan hasil ANC sampai persalinan dalam periode waktu 2019. Sebanyak 172 data memenuhi standar digunakan sebagai sampel. Variabel karakteristik ibu, faktor risiko kematian ibu, tingkatan faktor risiko ibu berdasar skor Poedji Rochjati sebagai variabel bebas, sedangkan variabel terikat adalah tindakan persalinan. Analisis data univariat dan bivariat dilakukan secara deskriptif dan analitik menggunakan uji chi square. Mayoritas ibu berumur 20-35 tahun (81,4%), berpendidikan dasar (94,2%), berstatus gizi normal (84,9%), tidak menderita anemia (80,2%), memiliki tekanan darah normal (70,9%), frekuensi kunjungan ANC antara 5-10 kali (65,7%), termasuk kategori kehamilan risiko rendah/KRR (86,6%), dan hampir seluruh ibu menerima tindakan persalinan normal pada persalinan sebelumnya (96,0%). Tindakan persalinan sebelumnya dan faktor risiko ibu berhubungan dengan tindakan persalinan terakhir yang diterima ibu (p-value=0,040; p-value=0,043).